Low back pain in adolescent female rowers : a multi-dimensional intervention study - Perich, D.; Burnett, A.; O'Sullivan, Peter; Perkin, C. (Wolters Kluwer Health - Adis International, 2011)
The aim of this study was to determine whether a multi-dimensional intervention programme was effective in reducing the incidence of low back pain (LBP) and the associated levels of pain and disability in schoolgirl rowers. This non-randomised controlled trial involved an intervention (INT) group consisting of 90 schoolgirl rowers from one school and a control (CTRL) group consisting of 131 participants from three other schools. All participants in the INT group underwent a multi-dimensional programme that consisted of an individualised exercise programme based on an individual musculoskeletal screening (Week 1) and a LBP education session conducted by a physiotherapist (Week 2) and performed an off-water-conditioning programme conducted by a Physical Education teacher. All exercises were undertaken during the season. Primary outcome variables collected at Start-season, Mid-season, End-season and Post-season included the incidence of LBP and related levels of pain and disability. Secondary outcome variables from the bio-psycho-social domain were measured at Start-season and End-season in the INT group only. The INT group had a lower incidence of LBP at Mid-season and End-season and displayed significantly better results than the CTRL group for improvers and non-improvers with respect to the levels of pain and disability. The INT group following the intervention also displayed improved physical fitness levels, sat with significantly less anterior tilt of the pelvis and lumbar kyphosis when in their usual sitting posture and demonstrated positive changes in their behaviour.The multi-dimensional approach to reducing the incidence of LBP, pain and disability in schoolgirl rowers in this study was effective. Several secondary outcome variables measured in the INT group considered to be of importance in LBP significantly improved. These included physical fitness (aerobic conditioning, lower limb and back muscle endurance and sit and reach flexibility) and seated posture (usual and slump sitting).